Isolation and selection of new biosurfactant producing bacteria from degraded palm kernel cake under liquid state fermentation - Jamal, Parveen; Mir, Shajrat; Alam, Md Zahangir; Wan Nawawi, Wan Mohd Fazli (Japan Oil Chemists' Society, 2014)
Biosurfactants are surface active compounds that are produced by different microorganisms. This study aims to introduce palm kernel cake as a novel substrate for biosurfactant production using a potent bacterial strain under liquid state fermentation. This study was primarily based on isolation and identification of biosurfactant producing bacteria that could utilize palm kernel cake as new major substrate. Potential bacterial strains were isolated from degraded palm kernel cake and screened for biosurfactant production with the help of drop collapse assay and by analyzing the surface tension activity. From the screened isolates, strain SM03 showed the best and consistent results and was therefore, selected as the most potent biosurfactant producing bacterial strain. The strain was identified as Providencia alcalifaciens (P. alcalifaciens) using Gen III Micro Plate Biolog Microbial Identification System.The yield of produced biosurfactant was found to be 8.3 g/l (w/v).